Evaluation of the ergonomic performance of residential kitchens through the comparative analysis of layout - Torres, Myrla Lopes (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The purpose of this work is to evaluate the ergonomic performance of residential kitchens through the comparative analysis of physical arrangements. An exploratory methodology was applied in four different types of kitchens layouts - U, L, parallel and horizontal - based on the arrangement of the stove, refrigerator and sink/counter. All of them were from apartments in João Pessoa, Paraíba. In order to evaluate this work environment, an ergonomic approach and a study of the layout, based on the principles of layout, were adopted. This research work concludes by proposing layouts for the types of kitchens that were investigated as well as making some ergonomic suggestions to the design of kitchens.